Quorum Sensing: Suatu Sistem Komunikasi Bakteri Fitopatogen, Peranannya Pada Proses Infeksi, dan Peluangnya sebagai Basis Pengembangan Strategi Baru dalam Pengendalian Penyakit Tumbuhan - Hadiwiyono Hadiwiyono (Universitas Gadjah Mada, 2009)
Previously, it is thought that bacterium is an autonomous unicellular organism with no capacity for collective behavior. Now the paradigm has changed since there are communication between intercell bacteria. The phytopathogenic bacteria are able to regulate gene expression which play an important role in infection process in the host plant. The gene expression regulation involves an intercell communication in the population and this is called as quorum sensing (QS). This paper reviews the QS as a communication system of phythopathogenic bacteria, its role in infection process on the host plant, and its opportunity as the basis of novel strategy development on plant disease control.